MENGKAJI POPULASI IKAN PUPUT (Ilisha elongata) YANG BERASAL DARI PERAIRAN KOTA TARAKAN - Firdaus, Muhammad; Salim, Gazali (Jurnal Harpodon Borneo, 2011)
Fish of puput is a kind of fish species found in the Juata waters of Tarakan City that many caught by local fishermen.  Fish of Puput frequently caught in the nets of local fishermen, especially around the Juata waters of Tarakan City, so that not rarely consider the fishing communities of this fish as a byproduct of fish because of low value (low-economically).The research method is a method of survey and research conducted this study belong to the type of exploratory research is to collect as complete information about Fish of puput (Ilisha elongata) in the waters around City of Tarakan.From the results research, the sex ratio between male and female fish is not an equilibrium that is 1: 3.1 where to fish of sex male as much as 33 tail and female sex of 102 tail.  The growth rate of male fish amounted to 0.013 or 1.3% every three months, while for the coefficient of female fish growth rate amounted to 0.023 or 2.3% every three months.  The rate of mortality from the catch of fishermen to fish the male sex has a value of about 2.2% every three months while the death rate from the catch of fishermen to fish the female type has a value of about 2.5% every three months. Keywords  :  Ilisha elongata, sex ratio, rate growth, rate mortality